2017
DOI: 10.1002/adma.201701075
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Tunable Hybrid Carbon Nanosheets with Solvatochromism

Abstract: The tunable photoluminescence of carbon-based nanomaterials has received much attention for a wide range of applications. Herein, a unique, broad-solvatochromic hybrid carbon nanosheet (CNS) synthesized through the hydrothermal carbonization of molecular precursors exploiting graphene oxide as a template is reported, resulting in the formation of clusters of carbon nanorings on the surface of graphene-oxide nanosheets. Under UV and visible-light excitation, the hybrid CNS exhibits tunable emission spanning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…For non-protic solvents (CP, EAC, and MC), the polarity decrease would cause red shifts in the emission wavelength of dissolved CDs (Figure 3a), and the UV-vis absorption wavelength blue shifts with the increase of the polarity (Figure 3c). In different non-protic solvents, dipole-dipole interaction plays a critical role in PL shifting, which is in accordance with the related reports [25,26,27].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For non-protic solvents (CP, EAC, and MC), the polarity decrease would cause red shifts in the emission wavelength of dissolved CDs (Figure 3a), and the UV-vis absorption wavelength blue shifts with the increase of the polarity (Figure 3c). In different non-protic solvents, dipole-dipole interaction plays a critical role in PL shifting, which is in accordance with the related reports [25,26,27].…”
Section: Resultssupporting
confidence: 92%
“…As shown in Figure 3c, with the polarity decrease of protic solvents (MT, EA, and IPA), the absorption peak of R-CDs red shift. The solvent-dependency of R-CDs originates from the hydrogen bond interaction between the protic solution and CDs [25,26,27]. For non-protic solvents (CP, EAC, and MC), the polarity decrease would cause red shifts in the emission wavelength of dissolved CDs (Figure 3a), and the UV-vis absorption wavelength blue shifts with the increase of the polarity (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…It is apparent that the Stokes shifts and lifetimes increase almost linearly with the increasing value of E T (30), which characterizes the ability to form HB [36]. Besides, it has been reported that stronger HB could lead to more interaction between functional groups and different solvents [25, 35]. Specific mechanism and reaction depiction of NCD formation are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al reported that their NCDs exhibited a tunable emission from a blue to green region in solvents with various polarities [24]. Apart from CDs, carbon nanomaterials like carbon nanosheet have also been reported to exhibit tunable PL in varying solvents, which require several synthetic precursors [25]. Therefore, the solvent-dependent effect is an effective post-treatment to optimize the PL properties of NCDs and further research is required to understand the influence of the interaction between solvents and surface states on the PL properties of NCDs.…”
Section: Introductionmentioning
confidence: 99%
“…43,[47][48][49][50][51][52][53][54][55][56][57] Additionally, signicant research reports have shown the solvent-dependent emission of carbon dots. [58][59][60] However, their hydrochromic properties are rarely discussed and for this reason, it is not known if some of these carbon dots also possess hydrochromic characteristics. Recently, two reports have proved that the carbon dots act as visual sensors of the water content in organic solvents.…”
Section: Introductionmentioning
confidence: 99%